Predation record of bees (Apidae: Hymenoptera) by assassin bugs (Reduviidae: Hemiptera) in the cerrado - Virley Gonçalves Rodrigues; Alexandre Camargo de Souza; Márcio Junior Pereira; Matheus Carneiro Heinzelmann; Hélcio Reinaldo Gil-Santana; Pedro Vale de Azevedo Brito; Herick Soares de Santana; Tatiana de Sousa Fiuza; Paulo Vitor Divino Xavier de Freitas; Everton Tizo Pedrosa; et al. (Acta Biológica Catarinense, 2025)
The predatory behavior of harpactorine assassin bugs on bees in different circumstances and locations is known and has been documented in the literature. In this paper we present three records of bee predation by two species of Zelus and one of Heniartes (Hemiptera: Heteroptera: Reduviidae: Harpactorinae), highlighting the predation behavior of the species in relation to stingless bees and the exotic bee Apis mellifera (Hymenoptera: Apidae: Apinae).